2005
DOI: 10.2527/2005.8361287x
|View full text |Cite
|
Sign up to set email alerts
|

Feed physical form and formic acid addition to the feed affect the gastrointestinal ecology and growth performance of growing pigs

Abstract: The effect of feeding a coarsely ground meal (COARSE) and a finely ground pelleted diet with 1.8% (as-fed basis) added formic acid (ACID) was compared with feeding a standard finely ground pelleted diet (STD) on the gastrointestinal ecology of growing pigs at different intervals after feeding. One hundred five castrated male growing-finishing pigs (initial BW 27 kg) were used. At a BW of 63 kg, 60 pigs were killed 0.5, 2.5, 4.5, 6.5, and 8.5 h after feeding, and samples from the gastrointestinal tract (GIT) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
105
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 37 publications
10
105
2
2
Order By: Relevance
“…Differences in the diet composition, buffering capacity and farming practices make it difficult to compare results from different studies. However, in general, significant effects on performance and intestinal microbiota were observed in trials with higher than 0.5% inclusion level of FA (Bolduan et al, 1988;Partanen and Mroz, 1999;Canibe et al, 2005;Franco et al, 2005), whereas studies using less than 0.5% FA did not report significant effects (Gabert et al, 1995;Knarreborg et al, 2002). This, together with the observations made in the present investigation, strongly suggest that it is the inhibitory, rather than stimulatory, effect of FA that improves the animal performance.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Differences in the diet composition, buffering capacity and farming practices make it difficult to compare results from different studies. However, in general, significant effects on performance and intestinal microbiota were observed in trials with higher than 0.5% inclusion level of FA (Bolduan et al, 1988;Partanen and Mroz, 1999;Canibe et al, 2005;Franco et al, 2005), whereas studies using less than 0.5% FA did not report significant effects (Gabert et al, 1995;Knarreborg et al, 2002). This, together with the observations made in the present investigation, strongly suggest that it is the inhibitory, rather than stimulatory, effect of FA that improves the animal performance.…”
Section: Discussionsupporting
confidence: 53%
“…This, however, would most likely reduce its value as a methionine source for the host. In studies with FA, a significant level of FA added in feed was found intact in the distal small intestine (Canibe et al, 2005). This explains why FA acted similarly both in in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Because organic acids are antimicrobial agents, their effects on ileal apparent amino acid digestibilities can be mediated via microbes of the digestive tract. Several authors have reported changes in bacterial counts and microbial metabolite concentrations in gastric and intestinal digesta of pigs fed diets supplemented with formic acid (Roth et al, 1992;Canibe et al, 2005). Reduced bacterial protein synthesis may contribute to the improved ileal apparent protein and amino acid digestibilities seen with the diets supplemented with organic acids (Partanen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%